2020
DOI: 10.3390/s20041078
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Algorithm for Mining Non-Redundant High-Utility Association Rules

Abstract: In business, managers may use the association information among products to define promotion and competitive strategies. The mining of high-utility association rules (HARs) from high-utility itemsets enables users to select their own weights for rules, based either on the utility or confidence values. This approach also provides more information, which can help managers to make better decisions. Some efficient methods for mining HARs have been developed in recent years. However, in some decision-support system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Experimental results have shown that the introduced structure has enhanced the runtime by orders of magnitude and significantly reduced memory requirements. Vo et al inherited a lattice-based approach [29], [30] to mine high utility association rules [31] and non-redundant high utility association rules [32].…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results have shown that the introduced structure has enhanced the runtime by orders of magnitude and significantly reduced memory requirements. Vo et al inherited a lattice-based approach [29], [30] to mine high utility association rules [31] and non-redundant high utility association rules [32].…”
Section: Related Workmentioning
confidence: 99%
“…The problem of association rule mining was first identified in [1], which received widespread attention. Several wellknown algorithms for association rule mining have been developed, such as Apriori [2], Eclat [39], FP-Growth [10], and NR-HARs [22] algorithms. Some well-konwn studies [38] [36] have attempted to elaborate efficient frequent itemset/pattern mining algorithms for transactional datasets or the data from the Internet of Things.…”
Section: Related Workmentioning
confidence: 99%
“…Commonly used mobility prediction models include association rule mining-based models [ 12 , 13 , 14 ], Markov chain-based models [ 15 , 16 , 17 , 18 , 19 ], and neural network-based models [ 20 , 21 ]. Association rule mining is based on the regularity and periodicity of the user itineraries, and location prediction is performed by mining the key stops and frequent routes of mobile users [ 12 ].…”
Section: Introductionmentioning
confidence: 99%